C–N coupling for 1,3,4-oxadiazole derivatives using RuPhos PdG4 catalyst: A Novel approach to efficient synthesis - Deepak Kumar; Girish Chandra Sharma; Mukesh Jangir (Results in Chemistry, 2025)
In this study, we report an enhanced methodology for the synthesis of 1,3,4-oxadiazole derivatives through Buchwald coupling reactions, utilizing the RuPhos PdG4 catalyst. The RuPhos PdG4 catalyst exhibited superior performance compared to traditional palladium-based catalysts, providing higher yields and greater selectivity under mild reaction conditions. The findings presented in this work pave the way for further exploration of RuPhos PdG4 in other coupling reactions and highlight its potential in advancing synthetic organic chemistry. The synthesized structures of all compounds were confirmed by conventional spectroscopic methods including 1H NMR, 13C NMR, and HRMS. Future research will focus on exploring the scope of this method across a broader range of substrates and applications.